RUVBL1/2 Complex Regulates Pro-Inflammatory Responses in Macrophages via Regulating Histone H3K4 Trimethylation - Zhang, Rui; Cheung, Chris Y.; Seo, Sang-Uk; Liu, Hang; Pardeshi, Lakhansing; Wong, Koon Ho; Chow, Larry M. C.; Chau, Mary P.; Wang, Yixiang; Lee, Ah Ra; Kwon, Woon Yong; Chen, Sheng; et al. (Frontiers in Immunology, 2021)
Macrophages play an important role in the host defense mechanism. In response to infection, macrophages activate a genetic program of pro-inflammatory response to kill any invading pathogen, and initiate an adaptive immune response. We have identified RUVBL2 - an ATP-binding protein belonging to the AAA+ (ATPase associated with diverse cellular activities) superfamily of ATPases - as a novel regulator in pro-inflammatory response of macrophages. Gene knockdown of Ruvbl2, or pharmacological inhibition of RUVBL1/2 activity, compromises type-2 nitric oxide synthase (Nos2) gene expression, nitric oxide production and anti-bacterial activity of mouse macrophages in response to lipopolysaccharides (LPS). RUVBL1/2 inhibitor similarly inhibits pro-inflammatory response in human monocytes, suggesting functional conservation of RUVBL1/2 in humans. Transcriptome analysis further revealed that major LPS-induced pro-inflammatory pathways in macrophages are regulated in a RUVBL1/2-dependent manner. Furthermore, RUVBL1/2 inhibition significantly reduced the level of histone H3K4me3 at the promoter region of Nos2 and Il6, two prototypical pro-inflammatory genes, and diminished the recruitment of NF-kappaB to the corresponding enhancers. Our study reveals RUVBL1/2 as an integral component of macrophages pro-inflammatory responses through epigenetic regulations, and the therapeutic potentials of RUVBL1/2 inhibitors in the treatment of diseases caused by aberrant activation of pro-inflammatory pathways.